FOREIGN POLICY RELATIONS BETWEEN SERBIA AND NORTH MACEDONIA 2006–2025. - Ilić, Dušan (Serbian political thought, 2025)
The aim of this article is to analyze the foreign policy relations between Serbia and North Macedonia in the period from 2006 to 2025, specifically from the moment Serbia reestablished its statehood after Montenegro’s secession. In this context, the first part of the paper offers a brief overview of the historical background of relations between Belgrade and Skopje during the final phase of the disintegration of Yugoslavia, i.e., during the era of the joint state FRY/SCG from 1991 to 2006. The central part of the paper focuses on the political, security, economic, and cultural relations between the two states in the period following Serbia’s renewed statehood. Specifically, through the issues of recognition of the so-called Kosovo,  the church dispute, then the status of national minorities but also participation in joint programs and initiatives, economic ties and interdependence, as well as humanitarian cooperation, which were the most topical and which aroused the most interest in political and media terms in both countries, we will try to consider the development of bilateral relations between Serbia and North Macedonia. They are highly complex, primarily due to issues of national and spiritual identity, as well as a shared cultural heritage, which has served both as a point of connection and a barrier to the national emancipation of Macedonians on one side and the modern understanding of Serbian identity on the other. The entire period of the dissolution of the former common state was marked by very poor bilateral relations, which culminated in Skopje's recognition of the secession of Albanian separatists in Priština in 2008. In recent years, relations between Serbia and North Macedonia have been warming on both the political and economic fronts, despite a change of government in Skopje in 2017 and the country’s accession to NATO in 2020. A particularly significant turning point was the recognition of the autocephaly of the Macedonian Orthodox Church by the Serbian Orthodox Church in 2022. The paper also explores the prospects for future relations between the two countries.
Keywords: Serbia; North Macedonia; Balkans; Church; NATO; identity